The effect of educational application in nursing internship clinical training on cognitive and functional skills and students' satisfaction - Maryam Khoshbakht-Pishkhani; Nazila Javadi-Pashaki; Niloufar Asgharzadeh Esfandi; Masoomeh Bagheri Koodakani; Saman Maroufizadeh; Ali Hamidi Madani (BMC, 2024)
Abstract Background Clinical education plays an essential role in shaping the nursing identity and is one of the central elements in the education of nursing students. Today, with the advancement of novel technologies, utilizing mobile phone-based technologies in the education of medical sciences is inevitable. Therefore, this study was conducted with the aim of investigating the impact of the urology educational application on nursing students' cognitive-functional criteria and satisfaction during the internship period. Methods This experimental educational intervention study was conducted during nursing students' urology internship course at Shahid Beheshti School of Nursing and Midwifery in Rasht. The data collection tools included a demographic characteristics questionnaire, cognitive skills scale, functional skills scale, and satisfaction scale (Stokes, 2001). The data were analyzed using SPSS software version 16, and a significance level was set at 0.05. Results Out of 48 studied students, 28 (58.3%) were males. The mean age of the students was 20.34 (SD = 1.51) years. In the application group, the mean of students' cognitive skills after the intervention significantly increased by 2.33 units (95% CI: 1.73 to 2.9) (t(23) = 7.97, P < 0.001, d = 1.626). By controlling the scores before the intervention, the adjusted mean score of cognitive skills in the application group was 0.56 units (95% CI: -0.16 to 1.28) higher than the traditional group; however, this difference was not statistically significant (F(1, 45) = 2.42, P = 0.127, η2 p = 0.051). There was no statistically significant difference between the mean score of students' functional skills in traditional and application groups (t(46) = 0.63, P = 0.532, d = 0.184). The total mean score of satisfaction with education in the application group was 83.0 (SD: 10.7). According to the values ​​of the quartiles, 75% of the students scored higher than 75.9, 50% scored higher than 83.9, and 25% scored higher than 91.1. Conclusion According to the results of this study, students' scores of functional and cognitive assessment and satisfaction with the application in urology clinical training were reported as favorable. Therefore, it is recommended that mobile phone-based technologies be used in students' clinical education and internships in combination with the traditional method.